Organizações sociais em Pernambuco: o desenho institucional do controle externo sobre os contratos de gestão - Melo, Paulo Hibernon Pessoa Gouveia de (2012)
The goal of this survey was to analyze the institutional model of the external control over the management contracts within the Financial Department of the state of Pernambuco in regards to its observance, by key players involved, of the contents of state laws which govern Social Organizations: the public administration sector, technicians within the Financial Department and members of its audit council. This study was based upon the following premises: that the new arrangements for the provision of public services through partnerships with Social Organizations, demand by the Financial Department, institutional models of objective inspection that strives for t ransparency when disclosing information; that the formatting process of such institutional models are dynamic, allowing that the contingencies experienced in its implementation might contribute to its improvement; and that these institutional drawings crea te impact upon the behaviour of the key players involved. The study was based upon documental analyses. The qualitative methodology of content analysis was chosen to analyze the data. The survey results showed that the institutional control of management c ontracts under the TCE - PE is characterized by its fragility as a mechanism for disclosure of information and therefore does not contribute to the reduction of information asymmetry that is established with the implementation of management contracts. Additi onally, this survey shows that the current institutional control model compromises and limits the performance of the Auditors Council to control these settings. Finally, it is shown that, despite its fragility, there was a low - compliance rate identified, a mong key players involved, in regards to implementing the current institutional model of control of management contracts; this implies a low institutionalization of this model. The results should provide a renewed discussion about the mechanisms of control of management contracts by TCE - PE, which may result in a new institutional model in order to bring out more transparency to partnerships with Social Organizations.